OPTIMASI PENGIRIMAN PAKET DI DESA REJOSARI MENGGUNAKAN METODE TRAVELLING SALESMAN PROBLEM - Adelia, Anggi; Aprilia, Jovika Sintia; Pratiwi, Aisyah; Soleha, Sri; Pratiwi, Suci Eka; Ramadhina, Diska; Darwanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Travelling Salesman Problem (TSP) is a crucial vehicle routing method in logistics management. This concept focuses on finding the minimum travel distance from an origin point to all destination locations, under the assumption that each point is visited exactly once before the vehicle returns to the starting point. Through the application of TSP, companies can minimize operational costs and improve travel time efficiency. Therefore, this approach serves as a highly effective solution for obtaining optimal routes in product distribution systems. This study was conducted to optimize package delivery routes in Rejosari Village using the Traveling Salesman Problem (TSP) algorithm. In the package delivery process, several obstacles arise, such as recipients not being at home, inaccurate addresses, and weather changes, which render delivery routes inefficient. These conditions require an optimal routing system that can increase courier time and travel distance efficiency.This research adopts a graph modeling approach, in which each delivery location is represented as a node and the distance between two locations as an edge weight. The coordinate data of the recipient locations are then processed into a distance matrix, which forms the basis for the TSP algorithm calculations. The algorithm is subsequently used to identify the optimal route that visits all delivery points with minimum distance before returning to the origin point. The results demonstrate that the application of the TSP algorithm reduces both total delivery distance and delivery time compared to conventional methods. Consequently, utilizing the TSP algorithm offers a highly effective solution to enhance the efficiency of distribution and logistics systems for package delivery in Rejosari Village.